Computer applications for finite mathematics and calculus - Ziegler, Michal R. (California : Dellen, 1981)
Contains fifty-five programs addressing topics in finite mathematics, probability and statistics, and calculus.
Students and instructors in courses such as finite mathematics, calculus for management and life sciences, statistics, or discrete mathematics.
System requirements: IBM-PC series computer system; 196K; DOS 2.1 or later; 1 dual-sided, double-density disk drive; IBM graphics adapter card and monitor to generate graphics.
Keywords: Mathematics -- Software; Calculus -- Software